2021
DOI: 10.1002/lio2.553
|View full text |Cite
|
Sign up to set email alerts
|

The biological underpinnings of radiation therapy for vestibular schwannomas: Review of the literature

Abstract: Objective Radiation therapy is a mainstay in the treatment of numerous neoplasms. Numerous publications have reported good clinical outcomes for primary radiation therapy for Vestibular Schwannomas (VS). However, there are relatively few pathologic specimens of VSs available to evaluate post‐radiation, which has led to a relative dearth in research on the cellular mechanisms underlying the effects of radiation therapy on VSs. Methods Here we review the latest literature on the complex biological effects of rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 133 publications
(147 reference statements)
0
4
0
Order By: Relevance
“…The exact mechanisms of radiation resistance of VS in patients are largely unknown but are likely related to several factors: (1) insufficient radiation dosages to initiate cell death, (2) efficient DNA repair systems, (3) tumor hypoxia preventing generation of radiation-induced reactive oxygen species, (4) altered expression of tumor suppressor and proto-oncogenes, (5) aberrant expression of cell cycle checkpoint proteins, (6) cumulative effects of the loss of function of the NF2-merlin tumor suppressor on cell proliferation, and (7) prolonged cell cycle arrest for DNA repair. 12,16,23-26 In our previous study, we showed that radioresistant VS cells mount a strong p21 response after radiation exposure (18 Gy), which can direct cells into cell cycle arrest and allow time for RAD51-associated repair of DNA damage. 21…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exact mechanisms of radiation resistance of VS in patients are largely unknown but are likely related to several factors: (1) insufficient radiation dosages to initiate cell death, (2) efficient DNA repair systems, (3) tumor hypoxia preventing generation of radiation-induced reactive oxygen species, (4) altered expression of tumor suppressor and proto-oncogenes, (5) aberrant expression of cell cycle checkpoint proteins, (6) cumulative effects of the loss of function of the NF2-merlin tumor suppressor on cell proliferation, and (7) prolonged cell cycle arrest for DNA repair. 12,16,23-26 In our previous study, we showed that radioresistant VS cells mount a strong p21 response after radiation exposure (18 Gy), which can direct cells into cell cycle arrest and allow time for RAD51-associated repair of DNA damage. 21…”
Section: Discussionmentioning
confidence: 99%
“…However, a subset of VS does not respond to SRS and continues to grow 13,14 . The exact mechanisms behind this radiation resistance are poorly understood 12,16 …”
mentioning
confidence: 99%
“…Merlin is a tumor suppressor protein that mediates cell proliferation through contact inhibition [ 212 ]. In VS, mutations in the NF2 gene on chromosome 22q12 cause deficiency or dysfunction of merlin, which leads to loss of contact inhibition and unregulated cell proliferation and tumorigenesis [ 212 , 213 , 214 ]. Normally, merlin colocalizes with receptor tyrosine kinases (RTK), such as ErbB2/ErbB3, epidermal growth factor receptor, and platelet derived growth factor receptor, and block several downstream pathways important for cell proliferation.…”
Section: Radiobiology and Radiation Resistance In Vestibular Schwannomamentioning
confidence: 99%
“…Merlin deficiency can promote tumorigenesis through dysregulation of the mitogen-activated protein kinase (Ras/Raf/MEK/ERK), phosphoinositide 3-kinases and protein kinase B (PI3K/Akt), proto-oncogene nonreceptor tyrosine kinase Src and focal adhesion kinase (FAK), Rac family small GTPase1 (Rac1) and p21-activated kinases (PAK), β-catenin, c-Jun N-terminal kinase (JNK), and mammalian target of rapamycin (mTOR) pathways. Deficiencies in merlin can also promote cell proliferation by releasing merlin inhibition of Yes-associated protein 1 (YAP1) in the Hippo pathway [ 212 , 213 ].…”
Section: Radiobiology and Radiation Resistance In Vestibular Schwannomamentioning
confidence: 99%